Deformation Simulation of a Soft-sheet Material Using Particle Method - Uehara, Takuya (European Journal of Applied Sciences, 2023)
In this study, the deformation of a soft?sheet material was simulated using a particle method. Herein, a square sheet made of soft material was modeled, and a rigid sphere was indented on the surface of the sheet. Considering the conventional scheme of the particle method, the sheet was assumed to consist of discrete particles. A spring-and-dashpot connection was applied as the interaction between the calculation particles. Consequently, dent deformation on the surface and overall deformation of the object were successfully realized. Furthermore, various deformation modes were observed at different interparticle parameters, confirming the validity of the present model for various materials. Subsequently, the free fall of a rigid ball on the surface of the sheet was simulated, and thus, repeated rebounds of the ball were properly reproduced. Therefore, it can be concluded that the present method can express both static and dynamic properties of various soft materials despite the simple algorithm and a small number of parameters.